(untitled) (Fiep Bulletin - online, 2014)
It was aimed to examine the prevalence of the pressure ulcers, risk factors, the elapsed time to develop it after being admitted to the hospital and the features examined by existing injuries. It is a documental and retrospective study with a quantitative approach performed in a government hospital in João Pessoa, Paraiba. The samples were composed by seventy medical records which have shown pressure ulcer registries. The data was analyzed by descriptive statistic. The prevalence of 5,6% was verified with masculine predominance (54,3%), patients over 65 years old (71,4%), patients from 31 to 50 days in-hospital (28,6%) and those that developed the injuries during the first fifteen days of hospitalization (75,7%). Risk factors more present were the underlying diseases (90%). Regarding the existing injuries (68,7%), the sacral and calcaneus areas (12,8%) and patients with stage II (35,7%). Patients more susceptible to develop pressure ulcers were identified in order to approve the care plan and install the appropriate preventive measures and treatment.